2018
DOI: 10.1016/j.jjcc.2018.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the extent of low-voltage zone on outcomes after voltage-based catheter ablation for persistent atrial fibrillation

Abstract: The extent of LVZ is an independent predictor for recurrence even after LVZ homogenization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 31 publications
1
52
0
Order By: Relevance
“…24,25 Many studies revealed that recurrence rate after AF ablation was significantly related with atrial fibrosis extent. [26][27][28][29][30] This fibrosis area might present as LVZs in endocardial recording. 8 Ablation strategy targeting these LVZs seems to be an effective way in AF ablation.…”
Section: Discussionmentioning
confidence: 98%
“…24,25 Many studies revealed that recurrence rate after AF ablation was significantly related with atrial fibrosis extent. [26][27][28][29][30] This fibrosis area might present as LVZs in endocardial recording. 8 Ablation strategy targeting these LVZs seems to be an effective way in AF ablation.…”
Section: Discussionmentioning
confidence: 98%
“…Low-voltage zones (LVZ) were arbitrarily defined as areas of a bipolar voltage of <0.5 mV, while silent areas (scars) translated into either no detection of electrical activity or a bipolar voltage of < 0.05 mV. Although several studies showed that patients presenting with increased LVZs (stages III and IV) present with increased post-ablation arrhythmic recurrences [44,46], there are several controversies regarding this technique.…”
Section: Left Atrial Fibrosis and Electroanatomic Mappingmentioning
confidence: 99%
“…LVZs defined as < 0.5 mV during SR are identified about 30% in patients with persistent AF [18,36,37] and 15% in patients with paroxysmal AF [31] . We categorized patients into Stage I to Stage IV according to the extent of %LVZ ([ Figure 1]), and reported that LVZ extent is still a strong predictor for recurrence even after LVZ Four stages of left atrial (LA) low-voltage zone (LVZ).…”
Section: Spatial Distribution Of Lvz Lge and Fibrosismentioning
confidence: 99%
“…Total %LVZ area was calculated as the percentage of LA surface area excluding the PV antral region, LAA orifice, and mitral valve, and LVZ was subsequently categorized as stage I (<5%), II (≥5% to <20%), III (≥20% to <30%), and IV (≥30%) according to previous publication. [37] homogenization [37] . The spatial distribution of LVZs is related to the extent of LVZ.…”
Section: Spatial Distribution Of Lvz Lge and Fibrosismentioning
confidence: 99%